2014
DOI: 10.1111/ina.12100
|View full text |Cite
|
Sign up to set email alerts
|

Extrolites ofWallemia sebi, a very common fungus in the built environment

Abstract: Wallemia sebi has been primarily known as a spoilage fungus of dried, salted fish and other foods that are salty or sweet. However, this fungus is also very common in house dust. The health effects of chronic exposure to mold and dampness are known to be associated with both allergens and various inflammatory compounds, including the secondary metabolites of building associated fungi and their allergens. IgE sensitization to W. sebi has been long reported from housing and occupational exposures. However, its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…include indole alkaloids, such as tryptophol and tryptophol acetate [26, 28], which are derived from the amino acid tryptophan. These aromatic alcohols are important signalling molecules that play a significant role in the control of morphogenesis in the fungal cells [59].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…include indole alkaloids, such as tryptophol and tryptophol acetate [26, 28], which are derived from the amino acid tryptophan. These aromatic alcohols are important signalling molecules that play a significant role in the control of morphogenesis in the fungal cells [59].…”
Section: Resultsmentioning
confidence: 99%
“…sebi represented the only known species of the genus Wallemia [19], thus reports regarding secondary metabolites ( Table 1 ) were limited only to this species. Wallemia sebi was reported to produce several bioactive metabolites, such as toxic wallimidione [26], walleminone and walleminol [2729], UCA 1064-A and UCA 1064-B [30, 31] and pigments [32, 33]. Walleminol (named also walleminol A) has been detected in food (jam and cake), both naturally and artificially contaminated with W .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Species in the W. sebi complex produce toxic metabolites, i.e., walleminol A, walleminone [7,8], azasteroid [9], and wallimidione [10], which may cause subcutaneous infections referred to as phaeohyphomycosis [11]. Some reports have suggested that species in this complex could be the causal agents for lung disease in farmers in Scandinavia, France, and China and allergic activity [12].…”
Section: Digital Signaturementioning
confidence: 99%